Use of chromosomal translocations with in situ DNA hybridisation to confirm localisation of human 5S ribosomal RNA genes. - Fennell, S J (1979)
Two cases of chromosomal translocations involving the long arm of chromosome 1 were investigated for 5S ribosomal gene localisation using in situ hybridisation. In the first family, there was an interstitial translocation of 1q25-32 to chromosome 5; the 5S genes remained on chromosome 1. In the second family, there was a translocation of 1q42-44 to chromosome 21q12; the 5S gene locus in this case was translocated. This shows that the 5S ribosomal genes are at position 1q42-44, confirming a previous assignment based on adenovirus-induced uncoiling and on a partial trisomy (Steffensen et al., 1977).